Accounts Payable and Receivable: Methods of Managing Them (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The stability of the financial position and professional reputation of an organization are considered important signs of its investment attractiveness. The size of receivables and payables, their ratio to the organization’s turnover, the number of counterparties, the history of mutual settlements and legal disputes regarding debt collection directly affect these characteristics. Accounts receivable and accounts payable are integral to any company’s balance sheet. The paper provides definitions of receivables and payables and describes the main methods of managing them.